Siloxane based Organic-Inorganic Hybrid Polymers and their Applications for Nanostructured Optical/Photonic Components - Rahmat Hidayat; Widiyanta Gomulya; Pina Pitriana; Ryan Irmansyah; Rany Miranti; Herman Herman; Sahrul Hidayat; Fitrilawati Fitrilawati; Akihiko Fujii; Masanori Ozaki (Institute for Research and Community Services, Institut Teknologi Bandung, 2012)
We have studied the preparation of organic-inorganic hybrid polymer precursors by sol-gel technique and their utilization for nanostructured optical components for photonic applications. The gel polymer precursors were prepared from siloxane modified by polymerizable acrylate groups, which can be processed further by photopolymerization process. Molecular structure characterizations by means of the FTIR measurements indicate the conversion of C=C bonds into C-C bonds after photopolymerization. This bond co nversion produces high cross-linking between the organic and inorganic moieties, resulting in thermally stable and chemically resistant thin polymer layer which provide unique advantages of this material for particular optical/photonic applications. By employing laser interference technique, gratings with periodicity between 400-1000 nm have been successfully fabricated. Application of those sub-micron periodicity of grating structure as active elements in optically pumped polymer laser system and Surface Plasmon Resonance (SPR) based measurement system have been also explored. The experimental results therefore also show the potential applications of this hybrid polymer as a building material for micro/nano-photonics components.